Knowledge management tools and strategies to be implemented for the effective and efficient management of public resources (2016)
We are in a changing society with constant information needs in which we require tools within an organization that vary according to the level of structure of the organization in which the decisions made by executives and / or managers are not properly structured and applied To a unique solution recipe, despite the fact that all organizations have as their object, to create economic value, which is where my research is located in the Group of contemporary studies of accounting, management and organizations with the efficient and effective taking of Decisions. Therefore, evaluation criteria and points of view must be considered and established before each presented situation, where the sources of information are external and subjective in environments of risk and uncertainty. For this, we must not only achieve sustainable competences by creating value, but carrying out planning and control functions closely linked to the cyclical nature of all processes, dynamic environment and adaptive organization and the permanent demands of users, so that finally Make the decisions with the supreme efficiency and effectiveness of each and every one of the strategic implementations, to achieve an excellent effect of performance of the organization.